2005
DOI: 10.1093/jhered/esi116
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of Iberian Horses Assessed via Mitochondrial DNA

Abstract: Despite a number of recent studies that have focused on the origin of domestic horses, genetic relationships between major geographical clusters still remain poorly understood. In this study we analyzed a 296 bp mtDNA fragment from the HVI region of 171 horses representing 11 native Iberian, Barb, and Exmoor breeds to assess the maternal phylogeography of Iberian horses. The mtDNA haplogroup with a CCG motif (nucleotide position 15,494 to 15,496) was the most frequent in Iberian and Barb breeds (0.42 and 0.57,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 21 publications
3
55
0
4
Order By: Relevance
“…1 reveals that the new haplocluster identified here is mainly spread over the Iberian area usually known as 'Celtic'. Following the traditional classification of the domestic animal native strains from this geographical area (see Royo et al, 2005 for more detailed information), the new cluster will be named hereafter Celtic-Iberian. Both Pyrenean populations have a haplotype assignable to the cluster East (Balkan type).…”
Section: Mitochondrial Dna Sequences Cluster Assignment and Differenmentioning
confidence: 99%
“…1 reveals that the new haplocluster identified here is mainly spread over the Iberian area usually known as 'Celtic'. Following the traditional classification of the domestic animal native strains from this geographical area (see Royo et al, 2005 for more detailed information), the new cluster will be named hereafter Celtic-Iberian. Both Pyrenean populations have a haplotype assignable to the cluster East (Balkan type).…”
Section: Mitochondrial Dna Sequences Cluster Assignment and Differenmentioning
confidence: 99%
“…Finally, the current research suggests that the two strains of the Asturcón pony breed derive from the same ancestral mare population. Most sequences analysed could be assigned to the Jansen et al (2002) D haplofamily which has been suggested to be the main representative of the ancestral Iberian horse population (Royo et al, 2005a). This is also truth for the out-ofSueve population of the black-coated Asturcón pony, which was obtained in areas with not many historical references on the existence of ancient local Asturcón herds.…”
mentioning
confidence: 71%
“…that the main matrilineal composition of the Asturcón pony belongs to the Jansen et al's (2002) haplotypic family D (Royo et al, 2005a). However, the mtDNA haplotypic variability in the black-coated Asturcón is much larger than that assessed in the bay-coated Asturcón (Royo et al, 2007;Álvarez et al, 2012) suggesting that the founder population of the black-coated Asturcón has a larger influence of foreign horse breeds.…”
mentioning
confidence: 92%
“…In terms of conservation, the observed phylogenetic relationships should help to preserve the more original genetic groups and protect their genetic variability. At a species level, horses possess relatively high haplotype diversity in the D-loop region of mtDNA (Kim et al, 1999;Vilà et al, 2001;Hill et al, 2002;Royo et al, 2005). The mean number of pairwise differences observed among all haplotypes was estimated at 8.81 or 2.72%.…”
Section: Discussionmentioning
confidence: 99%
“…The control region of the mitochondrial DNA (mtDNA) is, due to its high mutation rate, lack of recombinations and maternal inheritance, a very useful marker system for population and evolutionary biology. The mitochondrial DNA studies in horses have proved to be useful to characterize intra-and inter-breed relationships (Ishida et al, 1994;Ishida et al, 1995;Kavar et al, 1999;Kim et al, 1999;Vilà et al, 2001;Jansen et al, 2002;Hill et al, 2002;Mirol et al, 2002;Cozzi et al, 2004;Lopes et al, 2005;Royo et al, 2005;McGahern et al, 2006).…”
mentioning
confidence: 99%